Designing web site images : a practical guide - Berryhill, Gene. (Albany, N.Y. : Delmar; Thomson Learning, 2000)
Overview of design. Web graphic imaging. Compression techniques. Color and palettes. Graphic creation. Backgrounds. Buttons and other navigational graphics. Typography and text. Animating gifts. Collage, image maps, and navigation.
Keywords: Internet; Computer graphics; Web sites; Web sites -- Design; Computer graphics; Internet